Spatio-temporal evolution and distribution of cultural heritage sites along the Suzhou canal of China - Yan Huang; Shengdan Yang (Heritage Science, 2023)
Abstract The Grand Canal is one of the most important hydraulic engineering projects in Chinese history. The city of Suzhou has abundant and concentrated cultural heritage sites in the southern section of the Grand Canal. However, due to natural hazards, anthropogenic damage, and lack of human management, the cultural heritage sites have suffered irreversible damage. Digital preservation of these sites will make it possible to maintain their aesthetic and cultural value. This paper takes cultural heritage sites along the Suzhou Canal as its research subject and establishes a cultural heritage dataset using geographical information system (GIS). The paper uses geocoding and spatial analysis methods based on GIS, including nearest neighbor analysis, kernel density analysis, center of gravity analysis, and standard deviation ellipse. The paper explores the distribution of 104 cultural heritage sites along the Suzhou Canal across six historical periods and discusses the influencing factors for evolution of the distribution. The results show that: (1) major constructions on the Grand Canal water system were started in the Pre-Sui period and completed in the Sui and Tang Dynasties; (2) the degree of clustering of the distribution has increased since the Sui and Tang Dynasties until Modern Times; (3) the high-density area has been centered around the ancient city since the Pre-Sui period, and has shown a migration trend towards the Shantang Canal since the Ming Dynasty; (4) the center of gravity first moved from northwest to southeast along the Canal and then moved northeast towards the ancient city; (5) the aggregation of the sites peaked in the Qing dynasty (1636 CE-1911 CE), and the elliptical direction of distribution has become stable since then; and (6) the types of the cultural heritage in the evolution process are affected by the joint effects of natural and human factors, namely, elevation, canals, population, water transportation, and intangible cultural heritage, among which the canal characteristics play the decisive role. This study reveals the internal evolution mechanisms of the cultural heritage in the Suzhou Canal area and presents a scientific basis for the protection and utilization of the cultural heritage in other parts of the world.